2017
DOI: 10.1016/j.flatc.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Metamorphosis in carbon network: From penta-graphene to biphenylene under uniaxial tension

Abstract: The power of polymorphism in carbon is vividly manifested by the numerous applications of carbon-based nano-materials. Ranging from environmental issues to biomedical applications, it has the potential to address many of today's dire problems. However, an understanding of the mechanism of transformation between carbon allotropes at a microscopic level is crucial for its development into highly desirable materials. In this work we report such a phase transformation between two carbon allotropes, from penta-grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 67 publications
(111 reference statements)
6
23
0
Order By: Relevance
“…Based on the total energy calculations of a structure, all allotropes of graphene have less stability than graphene itself. As it is reported, graphenes' total energy is À9.23 to À9.28 eV per atom, [29][30][31] while this value for biphenylene is À8.82 eV per atom 30,32 and for graphyne is À8.3 to À8.51 eV per atom. 31,32 Nevertheless, allotropes of graphene have more strain sustainability than graphene itself; e.g.…”
Section: Introductionmentioning
confidence: 64%
“…Based on the total energy calculations of a structure, all allotropes of graphene have less stability than graphene itself. As it is reported, graphenes' total energy is À9.23 to À9.28 eV per atom, [29][30][31] while this value for biphenylene is À8.82 eV per atom 30,32 and for graphyne is À8.3 to À8.51 eV per atom. 31,32 Nevertheless, allotropes of graphene have more strain sustainability than graphene itself; e.g.…”
Section: Introductionmentioning
confidence: 64%
“…In contrast to graphene, which is, in fact, a one-atom-thick material, penta-graphene has nonzero thickness (1.2 Å). It was early theoretically proposed to be a thermodynamically and mechanically stable allotrope of graphene, however, further theoretical investigations have shown that it is mechanically, 31 thermodynamically, 32 symmetrically and topologically, 16 as well as energetically and kinetically unstable. 33 In particular, it has been shown that mutually perpendicular top and bottom sublattices create uncompensated mechanical stress, which consequently causes strong topological instability and bending of the 2D crystalline lattice.…”
Section: Toc Figurementioning
confidence: 99%
“…While theoretical studies predict that these phases are potential stable (although relatively less so than graphene), external stimuli or intrinsic defects may substantially reduce their stability. For example, Rahaman et al suggested that applying uniaxial loading transforms penta-graphene to a more energetically stable metallic isomer, biphynylene, [43] while Shahrokhi et al predicted that penta-graphene becomes much less stable under strain. [44] Among group III elements, especially for 2D aluminum (aluminene) and 2D boron (borophene), a number of allotropes have been theoretically predicted with somewhat complex multiatomic unit cells.…”
Section: Crystal Allotropes Of Elemental 2d Materialsmentioning
confidence: 99%
“…Qin et al demonstrated vapor phase deposition of selenene flakes, t = 5–15 nm and lateral dimensions ≈10 µm, in a tube furnace at ≈200 °C under flowing Ar . These flakes exhibited lateral growth along…”
Section: Synthesis Of Elemental 2d Materialsmentioning
confidence: 99%